2128. Predictors of Post-Discharge Prophylactic Antibiotics Following Spinal Fusion. (26th November 2018) - Warren, David K; Nickel, Katelin B; Banks, Ian; Han, Jennifer H; Tolomeo, Pam; Hostler, Christopher; Foy, Katherine; Fraser, Victoria; Olsen, Margaret A; ,
Abstract: Background: Discontinuation of prophylactic antibiotics <24 hours after surgery is recommended in multiple guidelines, but prophylactic antibiotics are still prescribed at discharge for some procedures. The objective of this study was to determine the prevalence and predictors of post-discharge prophylactic antibiotic use after spinal fusion. Methods: We established a retrospective cohort of patients aged ≥18 years undergoing spinal fusion between July 2010 and June 2015 at three teaching hospitals. We excluded patients with infections during the spinal fusion admission. Prophylactic antibiotics were identified at discharge. Results: A total of 9, 690 spinal fusion admissions were identified. The median age of patients was 57 years; 4, 425 (45.7%) were male; 1, 070 (11.0%) were trauma patients; and 352 (3.6%) had underlying malignancy. Antibiotic(s) were prescribed at discharge in 381 (3.9%) admissions. The most commonly prescribed antibiotics were trimethoprim/sulfamethoxazole (23.4%), ciprofloxacin (16.4%) and cephalexin (16.1%). Independent predictors of prophylactic discharge antibiotics are shown in the table. Conclusion: Post-discharge prophylactic antibiotics were uncommon after spinal fusion. Factors associated with use included hospital, trauma, prolonged surgery time, intra-operative antibiotics, plus patient factors, including obesity, malignancy, fluid and electrolyte disorders, valvular heart disease and high American Society of Anesthesiologists (ASA) score. Disclosures: All authors: No reported disclosures.